Handbook of Thermoplastic Elastomers - Drobny, Jiri George (Elsevier Science, 2014)
Handbook of Thermoplastic Elastomers, Second Edition presents a comprehensive working knowledge of thermoplastic elastomers (TPEs), providing an essential introduction for those learning the basics, but also detailed engineering data and best practice guidance for those already involved in polymerization, processing, and part manufacture. TPEs use short, cost-effective production cycles, with reduced energy consumption compared to other polymers, and are used in a range of industries including automotive, medical, construction and many more. This handbook provides all the prac.
11.2 Synthesis.
Keywords: Elastomers -- Handbooks, manuals, etc.; Thermoplastics -- Handbooks, manuals, etc.; elektronické knihy; electronic books